PENGARUH SIKAP, PERSEPSI KEGUNAAN, KOMPLEKSITAS, DAN TEKNOLOGI INFORMASI TERHADAP MINAT MENGGUNAKAN E-FILING (Studi Kasus Wajib Pajak Orang Pribadi di Kota Semarang) - Bella Fadhilah Chusaeni, 12.05.52.0150; Meita Oktaviani, Rachmawati (Students Journal of Accounting and Banking, 2017)
This study aims to examine empirically the influence of attitudes, perceptions of usefulness, complexit, and information technology of taxpayer interest in using e-filing. In this research, the researcher uses personal taxpayer population in KPP Semarang City. The method used is purposive sampling method. The sample used is 120 individual taxpayers in KPP Semarang City. The test equipment in this study used regression linier.Â The results of this study is the attitude and perception of usability does not affect the interest of using e-filing. Complexity and Information technology affects interest in using e-filing.Keywords : Attitudes, Perceptions of Usefulness, Complexity, Information Technology, Taxpayer Interest in using E-Filing